Qualidade da água e do pescado (tilápia-do-Nilo - Oreochromis niloticus) oriundos de pesque-pagues situados no estado de São Paulo - Siqueira, André Buzutti de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The fish and pay constitute recent activity, widespread throughout Brazil, one option for leisure, entertainment and services, lacking adequate regulatory framework and its necessary safeguards. Barely establishments installed, irregular, with inadequate management without technical supervision and inspec tion may account for environmental impacts and damage to public health. In this work proposed to evaluate the influence of seasonal variation, represented by the dry season and the rainy season on water quality and fish (Nile tilapia - Oreochromis niloticus) from five different fish and pay located in São Paulo. Physical and chemical analysis (temperature, dissolved oxygen and pH) were performed and microbiological cultivation of water (fecal coliform), analysis of the installation time of rigor mortis-full in specimens of fish and quantitative microbiological analysis (estimates of mesophilic aerobic microorganisms, of psychrotrophic aerobic microorganisms and bacteria of the genera Pseudomonas spp and Aeromonas spp.) of the surface slime, gills, of the abdominal cavity wash, skin and muscles with the Nile tilapia fillets. There was a significant difference (p <0.05) between the periods analyzed for temperature, dissolved oxygen and pH of the cultivation of water from fish and pay. For fecal coliforms, 20% (4/20) of the tanks of fish and pay were considered unsuitable for fish production during the rainy season. Both the surface slime, as to the gills, there was a reflection of that condition for, respectively, 10% (3/30) and 20% (6/30) with excess fecal coliform in periods of drought and rain. Regardless of the period after slaughter by brain destruction was found that the rigor-mortis reached its fullness five hours after is harvesting. Most of these parameters, represented by microbiological estimates of surface slime, gills, wash the abdominal cavity and the muscles with skin, there was a significant difference (p <0.05) ...

Os pesque-pagues constituem atividade recente, difundida por todo o Brasil, sendo uma opção de lazer, entretenimento e prestação de serviços, carecendo de adequado enquadramento regulamentar e suas necessárias salvaguardas. Estabelecimentos mal estruturados, irregulares, com manejo inadequado, sem supervisão técnica e fiscalização podem ser responsáveis por impactos ambientais e danos à saúde pública. Neste trabalho propôs-se avaliar a influência da variação sazonal, representada pela época da seca e época das chuvas, sobre a qualidade da água e do pescado (tilápia do Nilo - Oreochromis niloticus) oriundos de cinco diferentes pesque-pagues localizados no Estado de São Paulo. Foram realizadas análises físicas e químicas (temperatura, oxigênio dissolvido e pH) e microbiológica da água de cultivo (coliformes termotolerantes), análise do tempo de instalação do pleno rigor-mortis nos exemplares de peixes e análises microbiológicas quantitativas (estimativas de microrganismos aeróbios mesófilos, de microrganismos aeróbios psicrotróficos e de bactérias dos gêneros Pseudomonas spp. e Aeromonas spp.) do limo superficial, das brânquias, da lavagem da cavidade abdominal, da musculatura com pele e dos filés de tilápias do Nilo. Verificou-se que houve diferença significativa (p<0,05) entre os períodos analisados para a temperatura, o oxigênio dissolvido e o pH da água de cultivo dos pesque-pagues. Para coliformes termotolerantes, 20% (4/20) dos tanques dos pesque-pagues foram considerados impróprios para produção de peixes no período das chuvas. Tanto para o limo superficial, quanto para as brânquias, observou-se reflexo dessa condição para, respectivamente, 10% (3/30) e 20% (6/30) com excesso de coliformes termotolerantes nos períodos da seca e das chuvas. Independente do período, após o abate por destruição cerebral verificou-se que o rigor-mortis atingiu sua plenitude cinco horas após a...
Keywords: Peixe - Criação; Agua - Analise; Pescados; Microbiologia; Saúde pública; Fishes